Driving Digital Innovation and Growth: Empowering Tech Startups Through Cloud Computing in Nigeria - Abdulwahab, Shehu; Joshua Garba, Etemi; Bashir Ribadu, Mohammed (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Nigeria, with the Africa’s largest entrepreneurial ecosystem holds prospect for Tech startups. However, despite such potentials for growth and innovation, many Nigerian Tech Startups face numerous challenges; limited access to affordable and reliable computing resources, infrastructures and funding options. Developments in Information Technology (IT) have brought significant reliance on cloud computing where fast-paced Tech Startups driven by innovation explore as the foundation of their IT infrastructure and analytics to perform operations. We explore the fascinating nexus between cloud computing and Tech Startups in Nigeria, emphasizing how cloud technology act as a driver of digital innovation and economic growth. This study uses a conceptual firm level review to explore the phenomena, current state of the Nigerian Tech startup ecosystem, prospects, challenges and strategies to explore the full potentials of cloud computing in driving technological advancements. Nigeria’s cloud-powered Tech Startups is characterized with global presence, digital transformation, fin-tech innovations, e-commerce growth, artificial intelligence and data analytics, infrastructure development, government support, and startup ecosystem maturity. There is need for cloud-powered tech startups in Nigeria to be well-informed about the latest trends and opportunities to seize the potentials of cloud computing in driving innovation and growth in the country’s dynamic tech ecosystem.